Efficacy and safety of a bortezomib and reduced‐intensity cytarabine‐based protocol, TMC ALLR1, for relapsed childhood ALL in India. (5th June 2019) - Roy, Prakriti; Islam, Rubina; Saha, Debparna; Gogoi, Manash; Kumar Mishra, Deepak; Arora, Neeraj; Parihar, Mayur; Krishnan, Shekhar; Saha, Vaskar
Summary: The feasibility of bortezomib (BZB) in induction and reduced cytarabine doses in intensification was evaluated in children with relapsed acute lymphoblastic leukaemia (rALL) at a single centre in India. Of 55 children with rALL, 23 received supportive care and 7 refused treatment, with a median survival of 2 (interquartile range 1–6) months. Twenty‐two (88%) of 25 children who were treated achieved second remission and 9 (69%) of 13 had end‐of‐induction minimal residual disease of <10 −4 . The lower cytarabine dose was associated with decreased hospitalisation. One‐year event‐free and overall survival for the treated group was 74·7% (95% confidence interval 52–88) and 79·6% (58–91) respectively.